(untitled) (Research, Society and Development, 2020)
Onychomycosis are superficial infections that are characterized by the destruction of the nail bed and adjacent tissues with yeast fungi as important etiological agents of these diseases. In this context, the present study aimed to conduct a literature review on the genus Candida, emphasizing the main species responsible for onychomycosis, according to their epidemiological, pathogenic, immunological, diagnostic and pharmacological treatment. The research was developed in an exploratory and qualitative way, with a database approach of scientific publications, repositories and indexers. In view of the articles, dissertations, books and theses, C. albicas, C. tropicalis and C. parapsilosis has been presented as the main species of the genus Candida from a clinical and epidemiological, for nail infections with diagnosis centered on the clinical history of the laboratory tests, and more recently, by the use of image recording. The infection and dissemination process in nails occurs when virulence factors (adhesion, biofilms, pleomorphism, toxins, hydrolytic enzymes and phenotypic variability), overlap the defensive factors (microbiota, mechanical barriers and immune system). The treatment is based on the eradication of the infecting microorganism and regression of signs and symptoms, with three main pharmacological strategies, topical treatment (amorolfilina, ciclopirox), oral treatment (itraconazole and fluconazole) and combination therapy, however resistance mechanisms have been associated with these drugs. Given the above, the information present in this research serves as an aid for the consolidation of clinical - epidemiological knowledge that focuses on onychomycosis, caused by fungi of the genus Candida, including students, health professionals, academics and all society.